2021
DOI: 10.17275/per.21.38.8.2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of student-centered teaching methods used in mathematics courses on mathematics achievement, attitude, and anxiety: a meta-analysis study

Abstract: Mathematics is a branch of science that is used to understand and explore the relationship between the parts that make a great structure or a whole, the cause-and-effect relationships between the parts and the whole, all natural phenomena and, life in short. Students in Math must make progress in learning to follow teacher’s instructions and participating actively, using prior knowledge, building on it, and making sense of it instead of memorizing. Since student-centered teaching methods have frequently ben us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Student-centered learning process makes students better their achievements including attitudes compared to traditional learning. One example of student-centered learning is problem-based learning (Emanet & Kezer, 2020). They could not think critically since they found some difficulties in seeing the relevance of the presented topics.…”
Section: Discussionmentioning
confidence: 99%
“…Student-centered learning process makes students better their achievements including attitudes compared to traditional learning. One example of student-centered learning is problem-based learning (Emanet & Kezer, 2020). They could not think critically since they found some difficulties in seeing the relevance of the presented topics.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings contrast with those of Alsup, who discovered that students enrolled in Mathematics classes where traditional methods were used showed a greater decline in students' Mathematics anxiety than those enrolled in constructivist, active-learning classes [45]. Emanate showed that student-centered teaching strategies can help students who are anxious about Mathematics [46]. Altun stated that the type of teaching method adopted by Mathematics teachers can have an impact on how the students feel about Mathematics or how anxious they are [47].…”
Section: Resultsmentioning
confidence: 86%
“…So, how LC is connected to the mathematics class is briefly reviewed. Learner-centered instruction in mathematics is contributing factor enhancing learning performance and attitude (AY Emanet & Kezer, 2021) and it also increase the positive behaviour and confidence of the learner (Burns et al, 2014) which were implemented in different approaches and methods like problem-solving, collaborative or cooperative learning and others. The problem-solving approach is the central approach in mathematics teaching and learning activities in which learners are expected to participate actively.…”
Section: Learner-centered Instruction In Mathematics Classmentioning
confidence: 99%